2015
DOI: 10.4014/jmb.1507.07100
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Biological Control of Colletotrichum acutatum on Apple by Bacillus subtilis HM1 and the Structural Identification of Antagonists

Abstract: Bacillus subtilis HM1 was isolated from the rhizosphere region of halophytes for its antifungal activity against Colletotrichum acutatum, the causative agent of anthracnose. Treatment of postharvest apples with the cell culture or with a cell-free culture supernatant reduced disease severity 80.7% and 69.4%, respectively. Both treatments also exhibited antifungal activity against various phytopathogenic fungi in vitro. The antifungal substances were purified and analyzed by acid precipitation, gel filtration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Fungal co-culturing techniques have been used previously to mimic in vitro microbial interactions occurring in their natural environment and to identify new antifungal compounds ( Liu et al, 2001 ; Kim et al, 2015 ; Lopes et al, 2015 ; Ting and Jioe, 2016 ). We selected B. cinerea as a model to be used in fungal co-cultures and to induce the production of new SMs derived from fungal interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Fungal co-culturing techniques have been used previously to mimic in vitro microbial interactions occurring in their natural environment and to identify new antifungal compounds ( Liu et al, 2001 ; Kim et al, 2015 ; Lopes et al, 2015 ; Ting and Jioe, 2016 ). We selected B. cinerea as a model to be used in fungal co-cultures and to induce the production of new SMs derived from fungal interactions.…”
Section: Resultsmentioning
confidence: 99%
“…in biocontrol activity (Kong et al, 2012;Zhang et al, 2013). Recently, Kim et al (2015) reported that treating harvested apples with B. subtilis suspensions yielded a greater reduction in disease severity caused by C. acutatum than that with the culture filtrate. The isolates APEC136 and APEC170 greatly reduced the growths of C. gloeosporioides and C. acutatum pathogens in vitro, probably owing to their production of antifungal compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has investigated the efficacy of B. subtilis as a biocontrol agent targeting Colletotrichum species, highly destructive pathogens affecting various crops, including hot peppers and apples. B. subtilis has been shown to reduce anthracnose infections caused by C. gloeosporioides in red peppers ( Lee et al, 2020 ) and C. acutatum in apples ( Kim et al, 2015 ). Furthermore, a number of B. subtilis strains have been documented to impede the development of diverse fungal pathogens at varying degrees.…”
Section: Discussionmentioning
confidence: 99%